'Indie doc': documentary film and American 'independent', 'indie' and 'indiewood' filmmaking. Issue 1 (19th April 2016) - Tzioumakis, Yannis
ABSTRACT: The transformation of American independent cinema from a marginal sector of the US film industry in the 1980s into the popular 'indie' cinema in the 1990s and 2000s did not only affect fiction film. Feature documentaries also started losing their 'low-key, low-budget' label and moved away from the public service broadcasting ethos that had influenced the sector as a whole. By the 1990s, many documentaries were characterised by novel features, including commercially appealing subject matter, a strong awareness of the audience demographics they appealed to and the celebrity status achieved by certain documentarians, which gave these films increased marketing clout. More important, their distribution was increasingly undertaken by key 'indie' companies, whose savvy in handling product for niche markets helped the films find commercial success. By the 2000s, certain documentaries had become part of 'indiewood'. With mini-majors and the studios' newest specialty film divisions becoming increasingly integrated in the structures of global finance and distribution, documentaries were often released internationally, even reaching blockbuster status. The article examines documentary feature film's journey from the margins to the mainstream while also exploring the reasons behind the lack of contact between American independent cinema studies and Documentary film studies.